2013
DOI: 10.1002/nha.20003
|View full text |Cite
|
Sign up to set email alerts
|

Zombies, cyborgs, and other labor organizers: An introduction to representations of adult learning theories and HRD in popular culture

Abstract: Too often, educators, researchers, and practitioners in the fields of adult education and human resource development rely on traditional curricular materials and an academic body of knowledge for teaching, evaluating, and training adults. This assumes a coherent body of prior knowledge, assumptions, worldviews, and experiences in their students that can enable them to seamlessly connect to those materials. Of course, the reality is something different. Yet within the arena of popular culture, diverse individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Knowledge of adult learning (intra-cognitive generic competency), which includes competencies such as self-directive, relevant training content and learning by doing, proved to be the area that required the most improvement, followed by knowledge of OD (intra-cognitive technical competency). Amongst other intra-cognitive generic competencies, HRD graduates are involved with common culture programmes (Wright 2013), such as knowledge of how to interact with people, knowledge of work environment and knowledge of understanding people's feelings, as identified by this study. The study also confirmed that the intra-cognitive generic competencies predicted the expected interpersonal competencies of South African human resource development graduates.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Knowledge of adult learning (intra-cognitive generic competency), which includes competencies such as self-directive, relevant training content and learning by doing, proved to be the area that required the most improvement, followed by knowledge of OD (intra-cognitive technical competency). Amongst other intra-cognitive generic competencies, HRD graduates are involved with common culture programmes (Wright 2013), such as knowledge of how to interact with people, knowledge of work environment and knowledge of understanding people's feelings, as identified by this study. The study also confirmed that the intra-cognitive generic competencies predicted the expected interpersonal competencies of South African human resource development graduates.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…For example, students might explore the Western-oriented, nationalist portrayal of humanity's future in the Star Trek franchise (Ott & Aoki, 2001;Wright, 2013). Historical allegories can also be of value in the classroom; Sarantakes (2005, p. 78) describes Trek's Klingon empire and the "long, hostile confrontation that constantly teetered on the edge of full-fledged war" with the Federation as allegorical to the Soviet Union, and argues that the Romulans with their "Oriental tinge, isolated from the Federation, and in an alliance of sorts with the Klingons" represent the dangers of the Far East.…”
Section: Teaching: Creative Ways To Connect With Studentsmentioning
confidence: 99%
“…They emphasize the importance of "identify[ing] the best possible materials for this purpose and present[ing] them imaginatively" (1995, p. 7). These sentiments are echoed in the adult education literature (Diamantes & Ovington, 2003;Hutchins & Bierema, 2013;Laz, 1996;Marshall, 2012;Wright, 2013). As Wright (2013) notes, fandom often creates a bond among diverse individuals that provides them a shared social space for the examination of sensitive issues.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Few in AE “are very intentionally engaging popular culture as a tool of critical pedagogy” (Tisdell & Thompson, , p. 671). Horror media can be a cultural source for critical AE (Wright, ; ), and can be “used in effective critical pedagogical practices in university adult education” (Wright, , p. 756). AE researchers need to do more to make known how popular culture entertainment can be used as a site for pedagogy where viewers learn to resist hegemonic cultural discourses (Wright, ).…”
mentioning
confidence: 99%